Facts and Fiction: The Impact of Hypothermia on Molecular Mechanisms following Major Challenge - Michael Frink; Sascha Flohé; Martijn van Griensven; Philipp Mommsen; Frank Hildebrand (Mediators of Inflammation)
Numerous multiple trauma and surgical patients suffer from accidental hypothermia. While induced hypothermia is commonly used in elective cardiac surgery due to its protective effects, accidental hypothermia is associated with increased posttraumatic complications and even mortality in severely injured patients. This paper focuses on protective molecular mechanisms of hypothermia on apoptosis and the posttraumatic immune response. Although information regarding severe trauma is limited, there is evidence that induced hypothermia may have beneficial effects on the posttraumatic immune response as well as apoptosis in animal studies and certain clinical situations. However, more profound knowledge of mechanisms is necessary before randomized clinical trials in trauma patients can be initiated.